2011
DOI: 10.1097/olq.0b013e31820e64fd
|View full text |Cite
|
Sign up to set email alerts
|

Chemoprophylaxis Is Likely to Be Acceptable and Could Mitigate Syphilis Epidemics Among Populations of Gay Men

Abstract: Chemoprophylaxis offers promise as an acceptable and effective intervention for mitigating syphilis epidemics. The outcomes of a planned placebo-controlled syphilis chemoprophylaxis trial are eagerly anticipated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
37
2
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 41 publications
5
37
2
4
Order By: Relevance
“…Our finding of a gradually increasing trend in active syphilis infection among Australian blood donors may be due to the resurgence of syphilis in Australia, particularly among gay men, a trend also observed in other developed countries like the United Kingdom and the United States and Germany and Canada . The rate of infectious syphilis diagnosis increased more than twofold in the male population in Australia during the period of 2004 to 2007 and increases were almost completely limited to men who have sex with men .…”
Section: Discussionsupporting
confidence: 66%
“…Our finding of a gradually increasing trend in active syphilis infection among Australian blood donors may be due to the resurgence of syphilis in Australia, particularly among gay men, a trend also observed in other developed countries like the United Kingdom and the United States and Germany and Canada . The rate of infectious syphilis diagnosis increased more than twofold in the male population in Australia during the period of 2004 to 2007 and increases were almost completely limited to men who have sex with men .…”
Section: Discussionsupporting
confidence: 66%
“…Daily chemoprophylaxis to reduce syphilis incidence was reported to be acceptable among MSM. 32 Additionally, mathematical models have shown that syphilis chemoprophylaxis may have a substantial impact on the epidemic. 33 Daily doxycycline may only be appropriate for a subset of MSM for whom the benefits outweigh the possible risks.…”
Section: Novel Approaches To Sti Prevention In Msmmentioning
confidence: 99%
“…58 In an online survey conducted among MSM in Australia, over 50% of respondents stated that they would be likely to take daily pills to decrease their personal chance of syphilis infection, and over 75% were willing to take daily medication if it would result in a decrease in syphilis infections in the gay community. 59 A recent pilot study found that a daily dose of doxycycline to prevent syphilis infection in high-risk MSM was well-tolerated and that medication adherence was high. 60 Mathematical modelling of ongoing antibiotic prophylaxis in high-risk MSM has supported the effectiveness of such an intervention in significantly reducing new cases of syphilis in a community for a period of time, with a likely rebound in cases following discontinuation of the intervention.…”
Section: Key Prevention Interventions and How They Modify Syphilis Trmentioning
confidence: 99%
“…60 Mathematical modelling of ongoing antibiotic prophylaxis in high-risk MSM has supported the effectiveness of such an intervention in significantly reducing new cases of syphilis in a community for a period of time, with a likely rebound in cases following discontinuation of the intervention. 59 …”
Section: Key Prevention Interventions and How They Modify Syphilis Trmentioning
confidence: 99%